1983
DOI: 10.1159/000234835
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cytotoxic T Lymphocytes by a Schistosome-Derived Inhibitory Factor Is Independent of an Inhibition of the Production of Interleukin 2

Abstract: Schistosome-derived inhibitory factor (SDIF) was shown to inhibit lymphocyte proliferation. While SDIF is not toxic to lymphoid cells, the generation of cytotoxic effector cells was inhibited by SDIF in a mixed lymphocyte culture. This inhibitory effect was not attributable to the induction of suppressor cells, as SDIF also inhibited the development of nonspecific suppressor cell activity in 7-day cultures of unstimulated spleen cells. The interleukine 2-dependent proliferation of cytotoxic T lymphocytes of or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…Since the main effect of SDIF is to inhibit lymphocyte proliferation it could be postulated that antigen-induced lymphocyte pro liferation was reduced in vivo by the parasite-derived factor. In vitro experiments have shown the rapid in activation of SDIF in the presence of lymphoid cells [5]. Accordingly, the inactivation of SDIF given be fore the immunization could explain why no change in the specific IgE response was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the main effect of SDIF is to inhibit lymphocyte proliferation it could be postulated that antigen-induced lymphocyte pro liferation was reduced in vivo by the parasite-derived factor. In vitro experiments have shown the rapid in activation of SDIF in the presence of lymphoid cells [5]. Accordingly, the inactivation of SDIF given be fore the immunization could explain why no change in the specific IgE response was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Another characteristic of the immune response to parasites is a generalized immu nosuppression [3]. Schistosomes in particular have been shown to release an inhibitor of lymphocyte pro liferation (SDIF or schistosome-derived inhibitory factor) [4], This factor nonspecifically inhibits mito gen or antigen-induced lymphocyte proliferation as well as the generation of cytotoxic T cells [5]. It has been reported that immunosuppressive agents like cyclophosphamide or whole-body irradiation given together with the antigen, could modulate the ensuing IgE response [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the SDIF might actu ally be a catabolite of a host's material or a product of schistosomes itself. Previously, we have described the inhibition of lymphocyte proliferation by SDIF [2,7]. To test the hypothesis of a selective inhibition of some lympho cyte subsets, the effect of purified SDIF was tested on the proliferation of lymphoid cell lines of different origins.…”
Section: Discussionmentioning
confidence: 99%
“…The proliferation of all T cell lines tested so far was strongly inhibited by SDIF. Some of these T cell lines produce IL-2 (Jurkat, EL-4 and HSB-2) [13][14][15]; others are dependent on exogenous IL-2 (CTL-L) [8], It has been shown previously, using nor mal lymphocytes, that SDIF had no effect on IL-2 production but inhibited IL-2-dependent prolifera tion [7]. From our data we concluded that the inhibi tion of proliferation observed with SD1F is not medi ated through IL-2-dependent mechanisms, because IL-2-independent cells are also inhibited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation